1990
DOI: 10.1139/x90-153
|View full text |Cite
|
Sign up to set email alerts
|

Individual-tree diameter growth models for quantifying within-stand response to nitrogen fertilization

Abstract: Diameter-increment models for nitrogen-fertilized stands were developed using data from permanent research plots in northern Idaho. The equations partially resembled PROGNOSIS model diameter growth formulations. Results indicated that both initial tree size and initial stand density produced significant interactions with treatment to explain an individual tree's response to fertilization. Larger trees in a stand showed more fertilization response than smaller trees. Furthermore, individual trees in low-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The magnitude of fertilization responses was 33% to 97% for PAI of basal area and 25% to 92% for PAI of volume over the 20 years following treatment. This magnitude is comparable to the previous true fir studies (Heninger 1982;Miles and Powers 1988;Shafii et al 1990;Weetman et al 1976) and to averages for other sympatric forest species (Miles and Powers 1988;Weetman et al 1976). Based on results from only a few test plots that were measured for less than 10 years, Powers (1981) concluded that urea fertilization could improve height growth by 30% to 80%.…”
Section: Effect Of Treatment Interactionsupporting
confidence: 88%
See 3 more Smart Citations
“…The magnitude of fertilization responses was 33% to 97% for PAI of basal area and 25% to 92% for PAI of volume over the 20 years following treatment. This magnitude is comparable to the previous true fir studies (Heninger 1982;Miles and Powers 1988;Shafii et al 1990;Weetman et al 1976) and to averages for other sympatric forest species (Miles and Powers 1988;Weetman et al 1976). Based on results from only a few test plots that were measured for less than 10 years, Powers (1981) concluded that urea fertilization could improve height growth by 30% to 80%.…”
Section: Effect Of Treatment Interactionsupporting
confidence: 88%
“…Mortality was negligible in both fertilized and nonfertilized heavily thinned plots. Fertilizer-enhanced mortality was not found in a study of grand fir (Shafii et al 1990). …”
Section: Thinning Effectmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, there is a continuing need to model growth response to fertilization at the tree level. Such an example was provided by Shafii et al (1990), Stage et al (1990), and Hynynen (1993). However, there are no published individual tree basal area growth models that relate fertilization response to habitat type, rock type, stand attributes, and tree attributes and that are compatible with growth simulation models used in the region (Wykoff et al 1982).…”
Section: Introductionmentioning
confidence: 99%